Analysis of microRNAs and the microRNA-messengerRNA regulatory network in chronic alcohol exposure - Du, Ailin; Chen, Yingying; Qiao, Siyu; Dong, Jiaxing; Li, Yulin; Cao, Bokai; Zhao, Rongyu; Zhang, Ruiling (Frontiers in Pharmacology, 2024)
Introduction: Chronic alcoholism is one of the most common neurological diseases in modern society. However, the key mechanisms underlying learning and memory impairments caused by chronic alcohol exposure remain unclear. In this study, a microRNA-messenger RNA (miRNA-mRNA) network was constructed to explore the potential function of key genes in chronic alcohol exposure, their effects on the hippocampus, and their mechanisms which facilitate brain injury in mice. Methods: The Morris water maze test was used to assess the learning ability of mice in each group. Mitochondrial ATPase activity and H2S levels in the hippocampi of mice were determined. Differentially expressed miRNAs and mRNAs in the mouse hippocampus were identified using second-generation sequencing. Using the TargetScan, miRTarBase, and miRDB databases, we predicted miRNA target genes and constructed a miRNA-mRNA regulatory network. Furthermore, using the Gene Ontology and KEGG databases we performed functional enrichment and protein-protein interaction analyses. Real-time quantitative polymerase chain reaction (qPCR) and other methods were employed to verify the mRNA expression of related genes. Results: The Morris water maze test revealed that mice exposed to chronic alcohol exhibited a significantly reduced learning ability compared to the control group (p < 0.05). Compared with the control group, the activity of mitochondrial ATPase in the hippocampal tissue of alcohol-treated mice was significantly decreased (p < 0.01), suggesting brain injury. In the model group, H2S significantly increased in the mice hippocampi (p < 0.01), indicating that chronic alcohol exposure could activate cystathionineβ-synthase (CBS) and catalyze the mass formation of H2S, suggesting brain injury. A total of 208 differentially expressed miRNAs and 377 differentially expressed mRNAs were screened through bioinformatic analysis. Enrichment analysis indicated that the main pathways were involved in neurodegeneration and regulation of the Wnt signaling pathway. The PCR detected a significant downregulation in the expressions of FOS and EGR1 genes. Discussion: Consequently, chronic alcohol exposure may regulate the expression of FOS and EGR1 in the hippocampus through miR-222-3p, miR-132-3p, miR-212-3p, and miR-191-5p, reduce the activity of hippocampal mitochondrial ATPase, activate CBS, catalyze the large amount of H2S formation, and destroy the mitochondrial structure, resulting in decreased learning ability. Our findings revealed valuable genes and miRNAs for the study of chronic alcohol exposure.